2015
DOI: 10.2134/agronj14.0510
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Interception and Use Efficiency Contributes to Higher Yields of Newer Maize Hybrids in Northeast China

Abstract: A signifi cant trend of decreasing solar radiation has been observed in Northeast China over the past six decades. Such a decline in solar radiation could negatively impact maize (Zea mays L.) production. Th e improved cultivated hybrids may have adapted to these changes in solar radiation. In this study, four commonly cultivated maize hybrids in Northeast China were selected for a 2-yr fi eld study. Two hybrids were released in the 1970s and the other two were released in the 1990s. In comparison with the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
(30 reference statements)
3
21
0
Order By: Relevance
“…Consistent with previous studies (Colaizzi, Evett, and Howell 2011;Hao et al 2015b;Magaia et al 2017), water deficits decreased biomass at maturity, HI, and kernel weight. Instead of HI, an increase in biomass at maturity is the key driver for increased maize yield in the new hybrids (Zhao et al 2015). In this study, reduced biomass was only found at I 50 as compared to I 100 .…”
Section: Biomass Hi Kernel Weight Kernel Number and Yield Determimentioning
confidence: 49%
“…Consistent with previous studies (Colaizzi, Evett, and Howell 2011;Hao et al 2015b;Magaia et al 2017), water deficits decreased biomass at maturity, HI, and kernel weight. Instead of HI, an increase in biomass at maturity is the key driver for increased maize yield in the new hybrids (Zhao et al 2015). In this study, reduced biomass was only found at I 50 as compared to I 100 .…”
Section: Biomass Hi Kernel Weight Kernel Number and Yield Determimentioning
confidence: 49%
“…, Zhao et al. ). Under drought conditions, even though there were no differences in RUE and BM pm between the two hybrids, P1151HR produced more biomass during the post‐silking period than 33D49, which finally resulted in greater grain yield in P1151HR than in 33D49.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation (Duncan et al, 1967; Hammer et al, 2009) and empirical evidence (Lee and Tollenaar, 2007; Zhao et al, 2015) suggest that upright LAs combined with higher planting densities improve light distribution within the canopy. For example, modern hybrids intercept 14% more light than older hybrids (Lee and Tollenaar, 2007), and the increased light intercepted from leaves near the ear is positively correlated with grain yield (Ma et al, 2014; Zhao et al, 2015). Furthermore, modeling has suggested that LAs should gradually transition from upright in the upper canopy to less upright in the lower as this configuration would distribute solar energy across multiple leaves while maximizing the total solar energy absorbed by the canopy (Duncan et al, 1967; Zhu et al, 2010).…”
mentioning
confidence: 96%